2000
DOI: 10.1006/dbio.1999.9586
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression of the Wnt Antagonists Sfrp-2 and Frzb during Chick Development

Abstract: The Wnt genes are known to play fundamental roles during patterning and development of a number of embryonic structures. Receptors for Wnts are members of the Frizzled family of proteins containing a cysteine-rich domain (CRD) that binds the Wnt protein. Recently several secreted frizzled-related proteins (Sfrps) that also contain a CRD have been identified and some of these can both bind and antagonise Wnt proteins. In this paper we report the expression patterns of the chick homologues of Frzb, a known Wnt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(83 citation statements)
references
References 84 publications
5
78
0
Order By: Relevance
“…This is in particular the case of the Wnt antagonist Frzb-1, which is strongly expressed in the dorsal neural tube at the time of NC cell delamination. [114][115][116] Recent, interesting studies in the Xenopus embryo demonstrated that Frzb-1 promotes the dissolution of the basal lamina at the junction between the ectoderm and endoderm in the primary mouth primordium by decreasing levels of fibronectin and laminin transcripts. 117 Consistent with this view, overstimulation of the Wnt signaling pathway in vitro by LiCl or exogenous Wnt-1 or in vivo after electroporation of Wnt-1 or of a constitutively active form of β-catenin has been found to cause a marked inhibition of trunk NC cell delamination in birds.…”
Section: Molecular Players Of Emt In Nc Cellsmentioning
confidence: 99%
“…This is in particular the case of the Wnt antagonist Frzb-1, which is strongly expressed in the dorsal neural tube at the time of NC cell delamination. [114][115][116] Recent, interesting studies in the Xenopus embryo demonstrated that Frzb-1 promotes the dissolution of the basal lamina at the junction between the ectoderm and endoderm in the primary mouth primordium by decreasing levels of fibronectin and laminin transcripts. 117 Consistent with this view, overstimulation of the Wnt signaling pathway in vitro by LiCl or exogenous Wnt-1 or in vivo after electroporation of Wnt-1 or of a constitutively active form of β-catenin has been found to cause a marked inhibition of trunk NC cell delamination in birds.…”
Section: Molecular Players Of Emt In Nc Cellsmentioning
confidence: 99%
“…31 Tightly controlled expression of agonists and antagonists of the wnt signaling pathway is crucial for tissue differentiation as is observed for DDK-1, a potent antagonist of wnt signaling controlling head formation in Xenopus. 32 The expression of the wnt antagonists DKK3 and SFRP-2 33 indicates that synovial cells are undergoing developmental changes in those tissues with little immune activation. It has been suggested before that synoviocytes may perpetuate disease by an autonomous growth and activation process in late stage RA.…”
Section: Tissue Repair and Remodelingmentioning
confidence: 99%
“…Cell lines used for analysis included clone 46m Cells and Pax2 retrovirally transformed cells (designated clones 5,8,12,13,24,26,27,28). Each 100-mm plate contained 1 ϫ 10 7 cells.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most prominent genes activated in response to Pax2 encodes the secreted frizzled related protein, Sfrp2. The Sfrp proteins can negatively regulate signaling through sequestration of the Wnt ligands in the extra cellular space (7,28,29). Sfrp2 is expressed in the early polarized epithelial vesicle, in a subset of Pax2-expressing epithelia.…”
mentioning
confidence: 99%